Music mindfulness acutely modulates autonomic activity and improves psychological state in anxiety and depression - Ramirez, Christine; Alayine, Gertrude Asumpaame; Akafia, Cyril Selase Kwaku; Adichie, Kamsiyonna; Watts, Dash; Galdamez, Yizza; Harding, Lisa; Allsop, AZA Stephen (Frontiers in Neuroscience, 2025)
IntroductionAnxiety and depression reduce autonomic system activity, as measured by Heart Rate Variability (HRV), and exacerbate cardiac morbidity. Both music and mindfulness have been shown to increase HRV, and clinical approaches incorporating these interventions show promise as effective treatments for symptoms of anxiety and depression. Music mindfulness, which combines music listening with mindfulness activities, may provide unique and synergistic therapeutic benefits for stress management. However, to date, no studies have evaluated the physiological mechanisms underlying a community-based music mindfulness paradigm.MethodsWe used wearable technology to record electrocardiography and electroencephalography signals from participants with moderate symptoms of anxiety and depression during a community-based music mindfulness paradigm. We also assessed the impact of our music mindfulness session on participant’s psychological state.Results and discussionWe found that music mindfulness sessions acutely enhanced multiple measures of HRV and altered EEG power spectral density across various frequency bands in frontotemporal electrodes. Both live and virtual music mindfulness sessions also acutely reduced stress and altered participants’ state of consciousness; however, only live sessions fostered social connection. Additionally, the physiological and psychological effects of music mindfulness varied based on participants’ self-reported sex. Overall, our findings demonstrate that music mindfulness effectively engages autonomic and frontotemporal neural mechanisms, which may contribute to the treatment of anxiety and depression symptoms.